Prebiotic oligomerization and self-assembly of structurally diverse xenobiological monomers - Chandru, Kuhan; Jia, Tony Z; Mamajanov, Irena; Bapat, Niraja; Cleaves, H James (Scientific reports, 2020)
Prebiotic chemists often study how modern biopolymers, e.g., peptides and nucleic acids, could have originated in the primitive environment, though most contemporary biomonomers don't spontaneously oligomerize under mild conditions without activation or catalysis. However, life may not have originated using the same monomeric components that it does presently. There may be numerous non-biological (or "xenobiological") monomer types that were prebiotically abundant and capable of facile oligomerization and self-assembly. Many modern biopolymers degrade abiotically preferentially via processes which produce thermodynamically stable ring structures, e.g. diketopiperazines in the case of proteins and 2', 3'-cyclic nucleotide monophosphates in the case of RNA. This weakness is overcome in modern biological systems by kinetic control, but this need not have been the case for primitive systems. We explored here the oligomerization of a structurally diverse set of prebiotically plausible xenobiological monomers, which can hydrolytically interconvert between cyclic and acyclic forms, alone or in the presence of glycine under moderate temperature drying conditions. These monomers included various lactones, lactams and a thiolactone, which varied markedly in their stability, propensity to oligomerize and apparent modes of initiation, and the oligomeric products of some of these formed self-organized microscopic structures which may be relevant to protocell formation.